Himalayan Apiaceae - A comprehensive ecological and ethnobotanical evaluation - Abdullah Khoja, Aadil; Hamid, Mahpara; Hamid, Bilqeesa; Waheed, Muhammad; Azhar Jameel, Muhammad; Rainer W. Bussmann,; Shiekh Marifatul Haq, (Ethnobotany Research and Applications, 2024)
Background: Taxonomic patterns of ethnobotanical uses of plants support the hypothesis that families with the most species richness will have a large number of valuable species. However, certain plant families (e.g., Apiaceae) with specific bioactive characteristics are underrepresented due to changes in the cultural relevance of native plant species. Thus, developing a biocultural conservation strategy may benefit from an awareness of plant usage patterns. Methods: Ethnoecological data was collected through interviews and group discussions using semi structured and close-ended questionnaires. The data was subjected to hierarchical cluster analysis and ordination techniques (Principal Component Analysis) using multivariate software. Use value (UV), was quantitative indicators used to assess the homogeneity of the ethnobotanical data. Results: The present investigation documented a total of 18 plant species used by local communities for multipurpose. Majority of plants were used for medicinal purposes followed by fodder, and spices. Amongst the parts of plants, roots were the most utilized plant part with 28% of usage followed by leaves (25%). Gastro-intestinal disorders were treated with most species (32%), followed by musculoskeletal (17%). Most of the plant species are consumed in the form of infusion (31%) followed by decoction (25%). A heat map showed two distinctly separated clusters based on the degree of intensity of flowering timing of the flora and month. Out of 18 medicinal plants reported 15 medicinal plants were used for different ethnoecological uses other than medicinal values. We recorded only three species (Angelica glauca, Angelica archangelica, and Elwendia persica) used as flavoring agents especially in the local traditional cuisine. Highest UV was reported for Foeniculum vulgare (0.72), Elwendia persica (0.62). Conclusion: The study found plant uses were primarily medicinal and food-related; however other uses are also relevant. Our findings indicate that the most accessible or locally abundant plant species were the most beneficial to local residents. This is the first study of its sort in the region that linked ethnobotany, ecological links with plant uses. Keywords: Apiaceae; Ethnoecology; Flowering; Nativity; Photochemistry; Himalaya